Effect of Wi-Fi Wave Frequency 2.4 GHz to Water Content, Fat and Protein of Chicken Egg Based on Electromagnetic Waves Barrier (Journal of Basic and Applied Research in Biomedicine, 2022)
Chicken Egg is one of the most food consumption in public because of it's low price but high nutrition. In this research, chicken eggs placed 0,25 meter from wi-fi router and given electromagnetic waves barrier such as zinc and wood. The function of wi-fi router as radiating adder of wi-fi radio wave frequency 2,4 GHz. From the research,with the value of electromagnetic field is 18.24 ⨯ W/m, the highest reduction of water contect, fat dan protein is given from sample of chicken egg that placed 0.25 meter from wi-fi router without electromagnetic waves barrier. The value of reduction are 5.629 gram; 2.815 gram; 2.9 gram or 11.7%; 38.38%; 35.14%. Meanwhile, the sample of chicken eggs that placed 0.25 meter from wi-fi router and given electromagnetic waves barrier such as zink and wood, the higher reduction of water content, fat and protein is in wood. the value of water content, fat and protein are 3.0745 gram; 1.811 gram; 2.218 gram or 6.319%; 24.69%; 26.87%..